Study On Integrating A Multimedia Project Into The Constructivist Learning Environemnt And Its Implication On The Student Learning Process - Tai, Gillian Xiao Lian (2007)
This research sought to investigate the effect of integrating multimedia technology, via a multimedia project, into a constructivist learning environment, and its implications on the student learning process. The study was designed and structured so that students used a multimedia project to create a constructivist learning environment as well as to innovate a multimedia-mediated constructivist learning (MMCL) environment based on their coursework.